Pengaruh Modal Intelektual dan Ukuran Dewan Terhadap Return On Asset (Roa) (Studi Empiris Pada Perusahaan Manufaktur yang Listing di Bursa Efek Indonesia Tahun 2015-2017) - Rima Melati; Ahmadi Aidi (Neraca : Jurnal Akuntansi Terapan, 2021)
This research is a quantitative study which is intended to examine the effect of intellectual capital and board size on Return on Assets (ROA). The population of this research is manufacturing companies that are listed on the Indonesian Stock Exchange (BEI) in 2015-2017. The data used is secondary data, using data collection techniques in the form of documentation using annual financial reports and company annual reports. Return on Assets (ROA) is used to measure the profit earned by the company. Intellectual capital is measured using the VAIC value, while board size is measured by looking at the number of adult commissioners plus the number of boards of directors in a company. The results of this study indicate that intellectual capital and board size have a positive and significant effect on Return on Assets (ROA).